Seasonal variation of marine litter in Tangier Coast: Quantitative and classificative study - Adel Alshawafi; Mohamed Analla; Ebrahim Alwashali; Mustapha Aksissou (Open Journal of Environmental Biology - Peertechz Publications, 2020)
Tangier city is considered as one of the most important commercial city in Africa as a result of the new construction of its port, Tangier Med. This study evaluated the abundance of micro and macro debris in Tangier beach and their pollution degree. In 2015, a total of 16 samples were collected by season and size between 1 and 5mm.  The means of the results in macro debris are: 1651,4 g/season for plastic; 541,82 g/season for lumber/paper; 86,45 g/season for glass; 58,65 g/season for rubber; 42,5 g/season for metal; and 376,25 g/season for Cloth. The fragment presents the maximum rate with 18.75 g of a total of micro debris of 46,277g. The abundance of macro debris is maximum in season 2 (April-June), while the abundance of all types of macro debris is maximum in season 1 (January-March). The micro debris is very tiny throughout all the year.